Family Ownership and the Entrenchment Effect on Intellectual Capital Utilization: A Study of High-Technology Companies in Indonesia Dealing with the ASEAN Economic Community (AEC) - Bima Cinintya Pratama; Hardiyanto Wibowo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2017)
At the end of 2015, the Association of Southeast Asian Nations (ASEAN) brought into being the ASEAN Economic Community (AEC). Due to the AEC, the firms in ASEAN should utilize their resources more effectively and efficiently, so that the firms can survive and grow despite strong competition in the AEC. Indonesia, as the country with the largest economy in the region, needs to address this issue so that companies in Indonesia can face the challenges resulting from the AEC. This study aimed to examine the positive relationship between the intellectual capital (IC) and the financial performance of high-technology (high-tech) companies that are listed on the Indonesia Stock Exchange, and also to examine whether the entrenchment effect of family ownership exists. This study was conducted from 2008 to 2014. The final sample used in this study consisted of 31 companies with a total of 144 observations. This study used a panel data regression model analysis. The results showed that, for a company, IC has a positive impact on financial performance. This result indicated that the efficient and effective use of their IC will help the firms to achieve higher financial performance, and will be useful for dealing with the AEC. There was no evidence that the entrenchment effect exists in the family ownership of high-tech companies in Indonesia and hampers the utilization of IC.